2009
DOI: 10.1097/sle.0b013e3181bb4b65
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Laparoscopic Colorectal Surgery in High-risk Patients

Abstract: The aim of this retrospective study is to examine the feasibility and safety of laparoscopic colorectal resection for colorectal malignancies to determine "high-risk" patients. In our classification, 3 minor criteria including patients over 70 years of age, body mass index over 30 m/kg, and cigarette smoking and 5 major criteria including cardiac, pulmonary, renal, liver disease, and diabetes mellitus were selected to determine a high-risk group. Patients carrying 1 minor and 1 major criteria were classified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…It is well accepted that laparoscopic approach is equivalent in the treatment of rectal cancer and shows advantages of shorter hospitalization and faster recovery, lower blood loss and lower complications rates [19], especially in patients with low rectal cancer [20, 21, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…It is well accepted that laparoscopic approach is equivalent in the treatment of rectal cancer and shows advantages of shorter hospitalization and faster recovery, lower blood loss and lower complications rates [19], especially in patients with low rectal cancer [20, 21, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…7,8 In terms of respiratory mechanics and oxygenation, a number of recent studies have shown the usefulness of RM, which are applied during pneumoperitonium and laparoscopic surgery. [9][10][11][12][13] The duration of the maneuvers and the applied pressure values have been defined in detail in previous studies. Despite these detailed definitions, the effects of oxygen and oxygen percentage used during the process have not been an area of focus.…”
mentioning
confidence: 99%
“…The investigators used similar criteria to identify high-risk patients like we firstly defined in our previous study. 2 In our study, we defined five major criteria including cardiac, pulmonary, renal or liver disease, and diabetes mellitus and three minor criteria including age >70 years, body mass index >30 kg/m 2 , and smoking. The minor criteria were exactly the same in those two studies, but Kang et al did not determine all cardiac diseases as a major risk factor; rather, they determined congestive heart failure, valvular heart disease, and anemia as separate major risk factors.…”
Section: To the Editormentioning
confidence: 99%